Audit of the aetiology and prevalence of pulmonary hypertension in a tertiary hospital setting. Issue 3 (27th February 2013) - Suri, P.; Bull, N.; Worthington, A.; Gunawaran, P.; Reeves, G.; Bastian, B.; Collins, N.
Abstract Appropriate diagnosis and initiation of disease‐specific treatment is an important therapeutic goal in idiopathic pulmonary arterial hypertension. We evaluated the prevalence and aetiology of moderate‐to‐severe pulmonary hypertension in a cohort of patients referred for inpatient echocardiography, with significant pulmonary hypertension documented in 4.6%. Pulmonary hypertension complicating left heart disease was the most common aetiology, with idiopathic pulmonary arterial hypertension less frequent.